2004
DOI: 10.1074/jbc.m409954200
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation and Aggregation of Tau in Experimental Autoimmune Encephalomyelitis

Abstract: Axonal damage is a major morphological correlate and cause of permanent neurological deficits in patients with multiple sclerosis (MS), a multifocal, inflammatory and demyelinating disease of the central nervous system. Hyperphosphorylation and pathological aggregation of microtubule-associated protein tau is a common feature of many neurodegenerative diseases with axonal degeneration including Alzheimer's disease. We have therefore analyzed tau phosphorylation, solubility and distribution in the brainstem of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 52 publications
2
32
0
2
Order By: Relevance
“…In contrast, abnormally hyperphosphorylated forms of Tau and axonal transport defects present in several CNS degenerative diseases, including Alzheimer disease [50,51], are common features of selective progressive CNS degenerative processes. Recently, tissues from experimental autoimmune encephalomyelitis mice [37] and from MS [38,39] were also found to contain abnormally hyperphosphorylated Tau. In particular, the most severe form of MS, the PPMS variant, had prominent Tau pathology in CNS cells, including OLGs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, abnormally hyperphosphorylated forms of Tau and axonal transport defects present in several CNS degenerative diseases, including Alzheimer disease [50,51], are common features of selective progressive CNS degenerative processes. Recently, tissues from experimental autoimmune encephalomyelitis mice [37] and from MS [38,39] were also found to contain abnormally hyperphosphorylated Tau. In particular, the most severe form of MS, the PPMS variant, had prominent Tau pathology in CNS cells, including OLGs.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, gait abnormalities have been reported in corticobasal degeneration and in some clinical cases of frontotemporal lobar degeneration [32][33][34][35][36]. Furthermore, recent studies have also determined the presence of hyperphosphorylated Tau and/or Tau aggregates in CNS tissue from experimental autoimmune encephalitis (EAE), an animal model of demyelinating multiple sclerosis (MS) disease [37,38]. Noteworthy, hyperphosphorylated Tau was shown in OLGs in the most severe form of MS, primary progressive MS (PPMS), which manifests gait abnormalities from the very onset of the disease [39].…”
Section: Introductionmentioning
confidence: 96%
“…The PHFs and other forms of aggregated tau as the pathogenic forms of tau in AD consist of stable proteins that are impervious and resistant to post-mortal decay or suboptimal fixation conditions Braak et al, 2006). These pathogenic forms of tau might lead to microtubule breakdown and disruption of axonal transport (Schneider et al, 2004) as well as to the development of neuronal degeneration at selectively vulnerable brain sites (Braak et al, 2006;Goedert et al, 1998;Spillantini et al, 1996Spillantini et al, , 1998. The clear distinction between increased expression levels of tau and all pathogenic forms including fibrillary forms, oligomeric or aggregated tau is impossible with conventional staining and immunohistochemical methods.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in immunogens where oligomerization and/or conformation produce epitopes significant for immune protection, like Aβ, the choice needs be the whole antigen Brorsson et al, 2010;Vasilevko et al, 2010). But, in immunogens like tau the situation is more complex because of the occurrence of oligomerization and post translation modifications, like hyperphosphorylation, which causes local changes relevant for AD pathology that can respond to immunotherapy (Huang and Jiang, 2009;Schneider et al, 2004;Ubhi and Masliah, 2011). However, several studies have shown that oligomeric non-phosphorylated tau is an effective immunotherapeutic target, regardless of its state of phosphorylation, a topic that will be discussed here.…”
Section: Shortened or Partial Immunogensmentioning
confidence: 98%